Pengaruh Promosi Terhadap Keputusan Pembelian Mobil Mitsubishi Pajero Sport Pada PT. DIPA Otomotif Pekanbaru - Abibah, Anisa Zainatul; Gentawicara, Dinda (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research was conducted at PT. DIPA Otomotif Pekanbaru located at Jalan Jenderal Sudirman No.230 Pekanbaru. While this research is to determine the effect of sales promotion on purchasing decision of Pajero Sport Car at PT. DIPO Pekanbaru. In this research, Technical Data Analysis uses descriptive and quantitative analysis. With Simple Random Sampling method. This means that consumer respondents (subjects) who coincidentally meet with researchers can be used as samples, with a sample of 83 people. Based on the results of the research, it can be concluded that: discussion of simple linear regression with its regression equation Y = 17.839 + 0.594X using t test (83) = 1.989 while t count obtained 6.235 means t count > t table then Ho is rejected and Ha is accepted, which means there is a significant influence and has a positive relationship direction, namely if sales promotion continues to be increased, then the decision to purchase Pajero Sport Car at PT. DIPO Pekanbaru will increase. Meanwhile, the R_Square is 0.324, or 32.4%, indicating the contribution of the independent variable to the dependent variable. The remaining 67.6% is determined by other variables not included in this research model.